2006
DOI: 10.1128/aac.00365-06
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of a Thumb Domain Hepatitis C Virus Nonnucleoside RNA-Dependent RNA Polymerase Inhibitor

Abstract: A new pyranoindole class of small-molecule inhibitors was studied to understand viral resistance and elucidate the mechanism of inhibition in hepatitis C virus (HCV) replication. HCV replicon variants less susceptible to inhibition by the pyranoindoles were selected in Huh-7 hepatoma cells. Variant replicons contained clusters of mutations in the NS5B polymerase gene corresponding to the drug-binding pocket on the surface of the thumb domain identified by X-ray crystallography. An additional cluster of mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
35
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 52 publications
3
35
1
Order By: Relevance
“…A close examination of the binding pocket revealed that this substitution introduced a polar hydroxyl group in the otherwise hydrophobic pocket, thus significantly altering the hydrophobic interaction between the protein and the cyclopentyl group of AG-021541. Changes at residues M423, M426, and I482 were previously observed in in vitro resistance studies of compounds containing pyranoindole or thiophene-2-carboxylic acid cores, both of which bind to a similar region in the thumb domain of the polymerase as the dihydropyrone inhibitors analyzed in this study (10,17). The baseline prevalence of the resistance substitutions observed in this study in naturally occurring HCV isolates cannot be accurately determined due to the lack of adequate clonal sequences of the HCV genome.…”
Section: Vol 52 2008 In Vitro Resistance Studies Of Ag-021541 681mentioning
confidence: 64%
See 1 more Smart Citation
“…A close examination of the binding pocket revealed that this substitution introduced a polar hydroxyl group in the otherwise hydrophobic pocket, thus significantly altering the hydrophobic interaction between the protein and the cyclopentyl group of AG-021541. Changes at residues M423, M426, and I482 were previously observed in in vitro resistance studies of compounds containing pyranoindole or thiophene-2-carboxylic acid cores, both of which bind to a similar region in the thumb domain of the polymerase as the dihydropyrone inhibitors analyzed in this study (10,17). The baseline prevalence of the resistance substitutions observed in this study in naturally occurring HCV isolates cannot be accurately determined due to the lack of adequate clonal sequences of the HCV genome.…”
Section: Vol 52 2008 In Vitro Resistance Studies Of Ag-021541 681mentioning
confidence: 64%
“…In vitro resistance studies of various HCV inhibitors, including NS3 protease (20,21,24,41,44) and NS5B polymerase inhibitors (10,11,15,17,27,30,39,40,43), identified resistance mutations in the corresponding viral target regions, some of which have also been observed in subsequent clinical studies. A recent report indicated that resistance mutations observed in vitro were also developed in vivo after a 14-day monotherapy treatment with an NS3 protease inhibitor, VX-950, and correlated strongly with clinical outcome (33).…”
mentioning
confidence: 99%
“…The four representative palm-and thumb-binding NNIs selected in this study have been reported to effectively inhibit replication of subgenomic replicons with low toxicity. Noncompetitive inhibition of NS5B polymerase activity with respect to NTPs has been reported (2,15,16). Based on co-crystallization studies with NS5B, it has been proposed that allosteric inhibitors may lock the NS5B protein in an inactive formation by binding tightly to the protein (16,17).…”
mentioning
confidence: 99%
“…Although many small molecules have been reported to interact with the thumb II pocket, no specific analysis of the inhibition of de novo initiation has been reported (6,7,14,16,21,23,29,38,42). Filibuvir, also known as PF-00868554 (Fig.…”
mentioning
confidence: 99%